2007
DOI: 10.1021/ac061843x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Maturity and Quality of Fruit Using Noninvasive Extractive Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry

Abstract: Maturity is an essential factor that determines storage-life and final quality of most fruits and vegetables. Maturity monitoring is thus of paramount importance for postharvest handling and fruit quality regulation. Ideal analytical procedures for maturity investigation require high sensitivity, specificity, and high throughput and should be noninvasive. For the purpose of maturity differentiation, extractive electrospray ionization quadrupole time-of-flight mass spectrometry (EESI-QTOF-MS) is developed for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 55 publications
3
89
0
1
Order By: Relevance
“…In this case, liquid droplets representing the molecular composition of the bulk sample are transported by a stream of nitrogen gas into the EESI source [5,65,66,68,71,75,78,79], followed by ionization and detection. As a result, liquids with complex chemical compositions and high viscosities (e.g., serum, honey, edible oils, crude oils, ionic liquids, toothpaste, etc.)…”
Section: Samples Accessible For Analysis By Ambient Ionization Technimentioning
confidence: 99%
“…In this case, liquid droplets representing the molecular composition of the bulk sample are transported by a stream of nitrogen gas into the EESI source [5,65,66,68,71,75,78,79], followed by ionization and detection. As a result, liquids with complex chemical compositions and high viscosities (e.g., serum, honey, edible oils, crude oils, ionic liquids, toothpaste, etc.)…”
Section: Samples Accessible For Analysis By Ambient Ionization Technimentioning
confidence: 99%
“…Another technology, namely extractive electro-spray ionization coupled with quadruple time-of-flight MS was developed to monitor fruit maturity and provide different spectral fingerprints for fruit of different maturities (Chen et al 2007). The data collected from this study were also confirmed using principal component analysis.…”
Section: Analysis Of Flavour and Aroma Volatilesmentioning
confidence: 99%
“…Although matrix-assisted laser desorption ionization provides considerably better ionization efficiency than that of simple LDI [16], this can still be enhanced by electrospray post-ionization [17,18]. Another similar method is extractive electrospray ionization (EESI), which is also applied both for the ESI-MS analysis of fluid samples [19,20] and for the post-ionization of neutrals desorbed from solid surfaces [21,22].…”
mentioning
confidence: 99%